Effect of Brand Experience on Brand Loyalty: Mediating Role of Word of Mouth in the Mobile Money Service Brands - Matonya, juma (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2022)
This study examined the relationship between brand experience and brand loyalty in the presence of word of mouth as the mediator variable. Specifically, the study examined the effect of brand experience on brand loyalty and word of mouth (WOM), determining the effect of word of mouth on brand loyalty, and determining the mediation effect of WOM in the link between brand experience and brand loyalty. The study used an explanatory research design. Random sampling was used to select a total of 299 mobile money services users. This study used a structured questionnaire to collect data. Structural equation modeling was applied for data analysis in which SmartPLS 3 was utilized. The results indicate that brand experience has a positive and significant effect on brand loyalty and WOM. The findings also revealed that WOM had a positive and significant effect on brand loyalty. It was also found out that WOM partially mediated the link between brand experience and brand loyalty. This study concluded that brand experience and WOM were predictors of brand loyalty. It was also concluded that WOM plays a mediating role in the link between brand experience and brand loyalty. Thus, this paper recommended that mobile money network operators (MNOs) should provide a unique experience on every consumer-brand touch-point and devise strategies that would promote WOM recommendations that in turn would generate loyalty.